Analisis Pemanfaatan Flyash Sebagai Alternatif Bata Beton Untuk Meningkatkan Kuat Tekan - Triyanto, Romy Ade; Napitupulu, Robert; Juanda, Juanda (Manutech : Jurnal Teknologi Manufaktur, 2025)
Coal is an alternative energy that is used as energy for electricity generation and so on. The results of burning coal produce several wastes that are difficult to process and reuse, one of the wastes produced is fly ash, fly ash waste has several contents similar to cement material, one of which is silica. Use of fly ash as an additive to concrete bricks. This research aims to determine the effect of using fly ash as an additional material on compressive strength tests on concrete bricks and to determine the highest and lowest values ??of the composition of fly ash and sand. In this research, we will use the full factorial method to determine the number of specimens that will be made in the research, variations in the composition of fly ash: sand used are 10%: 60%, 20%: 50%, and 30%: 40%, with a ratio of cement: water fixed 2 : 1 and drying for 3 and 5 days. Compressive strength testing will be carried out on 6 specimens with 3 replications on each specimen so that the total number of specimens tested is 18 specimens. Based on the results of the best compressive strength test on specimen No.1 with a mixture of fly ash (10%): sand (60%), with a drying time of 3 days, the average maximum strength was 57.91 kg/cm2, while the strength test results The lowest pressure was produced on sample No. 4 with a composition of fly ash (10%) : sand (60%) with a drying time of 5 days which produced an average compressive strength test result which had a maximum value of 30.59 kg/cm2.